Enhancing Students’ English Vocabularies through Fun Digital Class - Muhammad Hasbi; Fitriyani Bakri; Abdul Halim; Mardiyanah Nasta; Nur Mutmainna Halim (PT. Global Research Collaboration, 2025)
The implementation of English language learning at the elementary school level in Indonesia continues to face significant challenges. One widely proposed solution to address these challenges is the integration of digital technology into English language instruction. The Fun Digital Class program aims to introduce and enhance elementary students’ vocabulary acquisition at SD Inpres Cambaya IV Makassar. Through the use of the Duolingo application, this program provides an engaging and effective method for English vocabulary learning, helping students build a strong foundation in language learning while fostering a positive attitude toward foreign language acquisition, particularly English. This program was conducted over a period of two months and involved 20 students from grades 4 to 6 (aged 10–12 years) who participated in an extracurricular English language program titled Fun Digital Class. The participants were selected using purposive sampling, considering that they shared a similar basic proficiency level in English, which was generally categorized as low. The program was implemented in three phases: the Preparation Phase, the Implementation Phase, and the Evaluation Phase. During its execution, the program successfully stimulated students’ enthusiasm and motivation in learning English vocabulary. As a result, participants demonstrated improved comprehension and mastery of English vocabulary by the end of the program. Furthermore, the majority of students expressed enjoyment and gratitude for the implementation of this program at their school, as it provided them with an engaging and enjoyable English learning experience.